Overview of business process modelling software - Chrobak, Paweł (Przegląd oprogramowania do modelowania procesów biznesowych w standardzie BPMN, 2011)
BPMN aims at consolidating and unifying the modelling of various business processes,from workflows and automated processes to designing choreographies used in determining commercial relations between business partners. What is more, the specification may refer to different scenarios: modelling business processes, the exchange of processes definitionsor process execution. It is obvious that not every tool supports all the functions. Some tools offer only modelling processes, others allow process simulation and analysis. Seventeen tools for the support of BPMN modelling have been chosen for the purpose of this article. The author analyses their functionalities, presents some leading software producers and looks atthe results of a survey on the usability of the tools among consultants and other people utilizing BPMN modelling
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 84-93
Keywords: business process modelling; business process modelling notation; BPMN software; BPMN vendors